(untitled) (Cardiovascular Journal, 2017)
Background: Patients of non-ST segment elevation acute coronary syndrome (NSTE ACS) is a large group who gets admitted in coronary care units. 12-lead electrocardiogram (ECG) provides the simple available and earliest objective information for risk stratification of NSTEACS. We tried to find out the association between magnitude of ST segment depression and angiographic severity in NSTE ACS patients. Methods: This cross sectional study was carried out in patients with NSTE ACS patients admitted into and underwent coronary angiography. A total number of 105 consecutive patients were included in this study. ST segment depression was measured and categorized according to magnitude of ST segment depression into three groups as Group I: No (<1mm) ST segment depression, Group II: 1-2 mm ( e1 to <2mm) ST segment depression and Group III: e 2 mm ST segment depression. Cumulative sum of ST segment depression and number of leads in ST segment depression also measured in all ECG leads. Angiographic severity was assessed by vessel score and Friesinger index. Significant CAD was considered if Friesinger index was e 5. Magnitude of ST segment depression was correlated with angiographic severity of coronary artery disease. Results: According to Friesinger index 56(53.33%) patients had significant CAD and 49(46.66%) patients had insignificant CAD. Magnitude of ST segment depression found to have significant relationship with severity of coronary artery disease (p<0.001). Number of leads in ST segment depression also revealed positive correlation (r = 0.446; p<0.001). Positive correlation was also found between sum of the ST segment depression and Vessel score (r= 0.435; p<0.001). Conclusion: Magnitude of ST segment depression is positively correlated with the angiographic severity of coronary artery disease in non- ST segment elevation acute coronary syndrome. Cardiovasc. j. 2017; 9(2): 116-121